Image Enhancement and Filters Using Fourier Transformation - Untay, Abegail P.; Cayabyab, Ma. Theresa C.; Yanday, Anna Clarice; Diza, Hazel Mae R. (Asian Journal of Multidisciplinary Studies, 2020)
Digital image enhancement techniques give a lot of choices for improving the visual quality of pictures or images. Image enhancement aims to process an image so that the result is more suitable than the original image for a specific application. This study presents the frequency domain and spatial domain methods for image enhancement, with particular reference to Fourier transformation and mask processing. Comparative analysis of frequency and spatial domain image enhancement algorithm was done and tested for different images with the aid of MATLAB. Upon testing the different algorithms, this study shows that two algorithms do great work on a particular kind of images. Spatial domain methods are good for removal of noises in an image and frequency domain methods are good for sharpening an image. On the other hand, the combination of the two domain techniques results in an image with a noise-free sharp image in very good quality.